Keputusan Keuangan Perusahaan: Sintesis Teori dan Bukti Empiris dalam Literatur Manajemen Keuangan - Aden Gunawan; Mukhtar Galib; Nurhidayanti S (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Corporate financial decisions play a crucial role in determining firm performance and firm value. These decisions consist of investment decisions, financing decisions, and dividend policy, which are interrelated and collectively shape a firm’s financial strategy. Although extensively examined in prior studies, the corporate finance literature reveals mixed and inconsistent empirical findings regarding the impact of these decisions on firm performance and value. Differences in economic conditions, firm characteristics, and methodological approaches contribute to these inconsistencies. This study aims to synthesize theoretical perspectives and empirical evidence on corporate financial decisions within the financial management literature. The research adopts a literature review approach with a synthesis method by systematically examining accredited national journal articles, reputable international journals, and relevant academic textbooks. The selected literature is analyzed using content analysis and classified into three main themes: investment decisions, financing decisions, and dividend policy. The findings indicate that investment decisions generally have a positive effect on firm performance and value, although the impact depends on investment efficiency and the quality of corporate governance. Financing decisions exhibit a non-linear relationship with firm value, where moderate leverage may enhance firm value, while excessive leverage increases financial risk. Meanwhile, dividend policy is highly contextual and influenced by growth opportunities, ownership structure, and capital market conditions. Overall, this study emphasizes the importance of an integrated approach to corporate financial decision-making and is expected to contribute theoretically to financial management literature while providing practical insights for financial managers in formulating effective and sustainable financial strategies.